Lá onde o santo perdeu as botas: iconografia e imaginária sacra em São José - Carmona, Raquel de Lourdes de Miranda e Silva (2019)
This dissertation seeks to present the iconography of the imaginary Josephine as the materialization of the sacred in the context of religious and sacred arts and its symbolic imagination, which is in the attributes and adornments that make up its iconographic ensemble, as well as its polysemy and the various perspectives. that the image shows within the scope of Brazilian popular Catholic religiosity. In this research, through the multidisciplinarity sought through the dialogues established over the field of Religious Studies, we list three Josephine models as significant representatives of its time, regarding the most evident aspects on the surface of an image: artistic school, its constructive technique and its Support. Therefore, Saint Joseph in Boots, Saint Joseph the Worker and Saint Joseph Sleeping were chosen as representatives of distinct periods, their imaginary and pertinences. In addition, we drew a brief ascension walk of the Josephine image highlighting part of the various titles, patronages and invocations granted by the Catholic Church. In order to fulfill our proposed objectives, we opted for a qualitative research with bibliographic approach, reading the highlighted images using Panofsky's iconological method for the analysis of the work of art, and then classifying each image according to Gilbert Durand's symbolic imagination.